Mitigating Climate Change through Restoration and Management of Coastal Wetlands and Near-shore Marine Ecosystems : Challenges and Opportunities - Crooks, Stephen; Herr, Dorothée; Tamelander, Jerker; Laffoley, Dan; Vandever, Justin (World Bank, Washington, DC, 2014)
There is overwhelming consensus amongst climate scientists that the Earth's warming in recent decades has been caused primarily by human activities that have increased the amount of greenhouse gases (GHGs) in the atmosphere. To mitigate the most serious impacts of climate change a range of different strategies to lower carbon dioxide (CO2) concentrations in the atmosphere are required. Building on outcomes and recommendations from various coastal carbon activities, this report explains the GHG dynamics of coastal wetlands and marine ecosystems (chapter two). The importance of coastal wetland and near-shore marine ecosystem carbon pools for climate change mitigation are described in chapter three, with a brief overview of the status of these systems, including drivers of change and implications of degradation of carbon pools, provided in Chapter four. Chapter five gives an overview of policy opportunities under ongoing United Nation Framework Convention on Climate Change (UNFCCC) negotiations and through revision of Intergovernmental Panel on Climate Change (IPCC) carbon accounting methodologies and eligible mitigation activities for developing as well as developed countries. The main recommendations for action are summarized in chapter six.